Chorioamniotic membrane senescence: a signal for parturition? - Behnia, Faranak; Taylor, Brandie D; Woodson, Michael; Kacerovsky, Marian; Hawkins, Hal; Fortunato, Stephen J; Saade, George R; Menon, Ramkumar (American journal of obstetrics and gynecology, 2015)
OBJECTIVE: Senescence is an important biological phenomenon involved in both physiologic and pathologic processes. We propose that chorioamniotic membrane senescence is a mechanism associated with human parturition. The present study was conducted to explore the association between senescence and normal term parturition by examining the morphologic and biochemical evidences in chorioamniotic membranes. STUDY DESIGN: Chorioamniotic membranes were collected from normal term deliveries; group 1: term labor and group 2: term, not in labor. Senescence-related morphologic changes were determined by transmission electron microscopy and biochemical changes were studied by senescence-associated (SA) β-galactosidase staining. Amniotic fluid samples collected from both term labor and term not in labor were analyzed for 14 SA secretory phenotype (SASP) markers. RESULTS: Morphologic evidence of cellular senescence (enlarged cells and organelles) and a higher number of SA β-galactosidase-stained amnion and chorion cells were observed in chorioamniotic membranes obtained from women in labor at term, when compared to term not in labor. The concentration of proinflammatory SASP markers (granulocyte macrophage colony-stimulating factor, interleukin-6 and -8) was significantly higher in the amniotic fluid of women in labor at term than women not in labor. In contrast, SASP factors that protect against cell death (eotaxin-1, soluble Fas ligand, osteoprotegerin, and intercellular adhesion molecule-1) were significantly lower in the amniotic fluid samples from term labor. CONCLUSION: Morphologic and biochemical features of senescence were more frequent in chorioamniotic membranes from women who experienced term labor. Senescence of chorioamniotic membranes were also associated with amniotic fluid SASP markers.
Keywords: chorion; porod v termínu; Term Birth; aging; premature birth; interleukin-8; Mitochondria; Chemokine CCL11; β-galactosidase; Chorion; Intercellular Adhesion Molecule-1; chemokin CCL11; Interleukin-6; ligand Fas; osteoprotegerin; fetal signals; senescence-associated secretory phenotype; lidé; Fas Ligand Protein; Adult; labor; dospělí; beta-Galactosidase; studie případů a kontrol; Cellular Senescence; Female; průřezové studie; těhotenství; faktor stimulující granulocyto-makrofágové kolonie; ženské pohlaví; Case-Control Studies; porodní děj; Cross-Sectional Studies; Labor, Obstetric; mladý dospělý; mezibuněčná adhezivní molekula-1; amnion; Humans; mitochondrie; Osteoprotegerin; Young Adult; delivery; sterile inflammation; plodová voda; stárnutí buněk; interleukin-6; Amnion; Pregnancy; Granulocyte-Macrophage Colony-Stimulating Factor; beta-galaktosidasa; pregnancy; Interleukin-8; Amniotic Fluid